2010
DOI: 10.1007/s10578-010-0178-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Zinc and Ferritin Levels on Parent and Teacher Reported Symptom Scores in Attention Deficit Hyperactivity Disorder

Abstract: Objective It has been suggested that both low iron and zinc levels might be associated with Attention Deficit Hyperactivity Disorder (ADHD) symptoms. However, the association of zinc and iron levels with ADHD symptoms has not been investigated at the same time in a single sample. Method 118 subjects with ADHD (age = 7–14 years, mean = 9.8, median = 10) were included in the study. The relationship between age, gender, ferritin, zinc, hemoglobin, mean corpuscular volume and reticulosite distribution width and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
48
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 19 publications
7
48
0
Order By: Relevance
“…Oner reported that ferritin and zinc deficiencies were associated with symptoms of hyperactivity in children (32). These results are consistent with our study.…”
Section: Discussionsupporting
confidence: 94%
“…Oner reported that ferritin and zinc deficiencies were associated with symptoms of hyperactivity in children (32). These results are consistent with our study.…”
Section: Discussionsupporting
confidence: 94%
“…We found a positive correlation between psychosomatic subscale of CPRS and ferritin. Other studies reported the relationship between the ADHD hyperactivity scores on Conners scale and low ferritin levels in their ADHD group [15][16][17]. Moreover, the results of the case control studies searching ferritin levels differ from each other.…”
Section: Discussionmentioning
confidence: 95%
“…Several researchers reported a link between zinc levels and ADHD symptoms [21]. Although the exact mechanism of how zinc may contribute to symptoms of ADHD is not known, there is evidence that zinc assists in both the production and regulation of melatonin, which is an important factor in the pathophysiology of ADHD due to its modulation of dopamine.…”
Section: Methodsmentioning
confidence: 99%